Analisis Parameter Nitrogen, Fosfor, dan Kalium terhadap Kerapatan Eceng Gondok di Danau Kerinci - Trio Pramana; Guntar Marolop; Siti Umi Kalsum (Universitas Batanghari Jambi, 2026)
Lake Kerinci has experienced environmental pressure due to increased nutrient inputs from domestic and agricultural activities, which may trigger eutrophication and excessive growth of water hyacinth (Eichhornia crassipes). This study aimed to analyze the concentrations of nitrogen (N), phosphorus (P), and potassium (K) and their relationship with water hyacinth density in Lake Kerinci. The research employed a quantitative approach with descriptive and correlational analyses. Water samples were collected from five sampling points in the Sanggaran Agung area of Lake Kerinci. Nitrogen and phosphorus concentrations were analyzed using UV-Vis spectrophotometry, while potassium was measured using an Atomic Absorption Spectrophotometer (AAS). Water hyacinth density was determined using the quadrat method. Data were analyzed using descriptive statistics and Spearman correlation analysis. The results showed that nitrogen concentrations ranged from 1.62 to 6.33 mg/L, while phosphorus concentrations ranged from 0.05); however, both relationships were not statistically significant. The relationship between potassium concentration and water hyacinth density could not be analyzed due to data limitations. These findings suggest that water hyacinth growth in Lake Kerinci is influenced not only by nutrient concentrations but also by other physical and environmental factors.